Supercritical fluid extraction of Rumex Acetosa L. roots: Yield, composition, kinetics, bioactive evaluation and comparison with conventional techniques - Santos, Ênio Rafael de Medeiros (2021)
In this study, Rumex Acetosa extracts were obtained from extraction techniques with supercritical fluid (SFE), Soxhlet and low pressure solvent extraction (LPSE). In the SFE, it was evaluated the effect of the process variables (temperature, solventflow rate,pressure andcosolvent concentration) onthe extraction kinetics, yield and extract solubility. In the Soxhlet extraction, it was evaluated the usage of ethanol, acetonitrile, isopropanol and tert-butyl alcohol, while in LPSE extraction, it was used ethanol as solvent. The phenolics total content (TPC), antioxidant capacity (IC50) and extract composition were determined. The yield obtained ranged from 0.2 to 8.3%. The SFE extraction has demonstrated great efficiency in the extraction of phenolic compounds (anthraquinone and stilbene). The trans-resveratrol concentration in the extracts ranged between 1.03 and 3.52 mg/g, depending on the technique used, the values of IC50 and TPC ranges from 10.67 to 163.43 g/mL and 27.63 to 157.04 mgEAG/g, respectively